Philippines: Strength and Weakness of Science Curricula - Dadan Sumardani (SEJ (Science Education Journal), 2021)
The Philippines is a country in Asia which in its curriculum requires English as the medium of Instruction, even so the scientific ability of students in the Philippines is not so good as seen based on PISA 2018. Many things can be learned from the curriculum of other countries so that it can be an illustration of how the curriculum should be perfected. This article provides an overview of how the process of science lessons taught in Philippine schools and the obstacles it faces. The method used is In depth Interview with qualitative analysis. This article suggests that the medium of instruction is important for the continuity of the learning process in the classroom, at the same time this can be a lesson for schools in any country that will carry out the bilingualization process in their schools or use a second language as a medium of instruction, to pay attention to the long-term effects on students and conduct research. depth before applying the approach.